Kinesetic Stimuli as A Study of Motion Development in the Creating of Choreography of Zapin Adab and Budi - Martozet Martozet; Nurwani Nurwani; Merdy Roy Sunarya Togatorop (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to describe the study of the choreography creation of Zapin Adab and Budi, starting with the kinesthetic stimulus popularized by Jacqueline Smit. The traditional silat and Zapin of the Malay people of East Sumatra were used as a source of movement development in producing the new choreography by Zapin Adab and Budi. The method used in this study is qualitative by conducting field observations in obtaining data, interviews, documentation, and literature studies related to Silat and Zapin traditions of the Malay community of East Sumatra. The silat movements that are used as a source of development are the praying, stabbing, elbowing and kicking motifs. While the traditional zapin motifs that are used as a source of movement development are the Opener or Worship motifs, Greetings, Alif, Drag, and Broken. Movement development is carried out based on development studies by emphasizing the elements of motion, namely energy, space, and time. After experiencing the development process, movements with new forms and new styles were born, which were different from the original motifs. Meanwhile, of the three elements of motion, namely energy, space, and time, only the spatial element is the most dominant in producing new motifs, different in shape and character from the original motif. While the elements of energy and time are to provide reinforcement in forming the space for movement and the rhythm of movement naturally. From the results of the creation, it can be concluded that kinesthetic stimulation in the creation of dance can give birth to motion with new and unique forms through the development of elements of motion, energy, space, and movement.